Gravitation and inertia - Ciufolini, Ignazio, 1951- (Princeton series in physics., 1995)
Einstein's standard and battle-tested geometric theory of gravity - spacetime tells mass how to move and mass tells spacetime how to curve - is expounded in this book by Ignazio Ciufolini and John Wheeler. They give special attention to the theory's observational checks and to two of its consequences: the predicted existence of gravitomagnetism and the origin of inertia (local inertial frames) in Einstein's general relativity - inertia here arises from mass there.